Modul pružnosti přírodního kamene - Hoduláková, Michaela (Vysoké učení technické v Brně. Fakulta stavební, 2015)
Hodnota modulu pružnosti betonu závisí na jeho složení (zejména na použitém kamenivu). Jelikož v současném stavebnictví neexistuje žádná ucelená literatura týkající se modulů pružnosti jednotlivých typů kameniva, je tato práce zaměřená na zkoušky a porovnání modulů pružnosti vybraných druhů hornin používaných pro výrobu drceného hrubého kameniva do betonu. Moduly pružnosti se zjišťují statickou a dynamickou metodou. Práce se také věnuje modulu pružnosti žuly v rozdílném stádiu zvětrání.

The value of the modulus of elasticity of concrete depends on the concrete composition (particularly on the aggregate used). The contemporary construction industry literature lacks comprehensive studies of the modulus of elasticity for each type of the rock stone. Therefore, this study focuses on testing and comparing the modulus of elasticity of selected types of rock stones used for the production of crushed coarse aggregates into the concrete. The modulus of elasticity are determined by static and dynamic methods. The work also deals with the modulus of elasticity of granite in different stages of weathering.
Modulus of elasticity of natural stone
Keywords: Beton; horniny; kamenivo; modul pružnosti; pevnost v tlaku; statická zatěžovací zkouška; rezonanční metoda; ultrazvuková metoda; zvětrávání; Concrete; rock stones; aggregates; modulus of elasticity; compressive strength; static load test; resonance method; ultrasonic pulse method; weathering